Producing Your Own Video Program: AEC340/WC022, rev. 7/2021 - Telg, Ricky; Beattie, Peyton (EDIS, 2021)
This 4-page publication of the UF/IFAS Department of Agricultural Education and Communication provides an overview of what you should consider as you create your own video program. Minor revision by Ricky Telg and Peyton Beattie.